Students' perceptions towards ICTs used for emergency remote learning in higher education during Covid-19 : a case study of the NWU Mafikeng Campus - Zethi, Thato Pecunia (North-West University (South Africa), 2023)
Communication plays a vital role in all spheres of activity where it helps people to share and understand meaning. This includes Teaching and Learning (T&L) whose key components are content and communication. It is from this perspective that the main thesis advanced in this study is that T&L during Covid-19 was a communication issue. The Covid-19 pandemic and its bearing on higher education has attracted wide scholarly interest, most of which was conducted from an education, digital transformation, and other perspectives. The uniqueness and contribution of this study is that T&L during Covid-19 is studied from a communication perspective focusing on how emergency remote teaching and learning (ERT&L) affected tuition delivered to learners of a traditionally residential university through electronic communications media. To address this concern, students' perceptions towards Information Communication Technologies (ICTs) used for ERT&L in higher education during Covid-19 were explored among North-West University (NWU) students at the Mahikeng Campus. The study departs from a premise that in residential universities, T&L usually takes place through face-to-face interpersonal communication. However, T&L during Covid-19 involved an abrupt and unplanned provision of learning activities to remotely and disparately located students through new media or ICTs, new tools that as Kist (2005) suggests required new literacies, additional social practices, skills, strategies, and dispositions by both students and lecturers to fully exploit their potential. Data was collected through focus group discussions with a sample of thirty-six (N = 36) students at different levels of their qualification programs to establish which ICT strategies the NWU adopted in response to the Covid-19 outbreak, explore students' experiences of ICTs used for T&L during Covid-19, discuss students' views towards ICTs used for ERT&L during Covid-19 and apply a communication analysis of the process. Two communication theories, Media System Dependency Theory (Ball-Rokeach & Defleur, 1976) and Transactional Model of Communication (Barnlund, 1970) are applied as an analytic framework. Findings suggest that different ICTs were used for T&L during Covid-19 and students' perceptions of the ICTs derive from both positive and negative experiences students had while using them. Both internal and external factors such as lack of training, understanding, and skills to operate these ICTs, limited access to digital technology devices, and connectivity issues were notable challenges that affected students' experiences and perceptions of these technologies. Together, these challenges can be surmised from a communications perspective as noise which affected effective communication, which in this context refers to the learning process. The findings also echo previous studies that revealed various affordances that digital technologies brought in the enhancement of independent learning skills required in higher education. Notable examples include among others the ability by students to study from the comfort of their homes, improved engagement with lecturers as well as the v ability to listen to recorded lectures at one's own convenience. From a communication perspective, it can be concluded that learning during Covid-19 was affected by various 'noises' around the channels of communication used. As a result, learning progress was generally challenging. Four conclusions are conceivable. First is that T&L was variously affected by the ICTs deployed to transfer learning. This as it (T&L) shifted from the classroom to online platforms through new media that required new literacies by students and lecturers who unfortunately were both unprepared to fully exploit their potential. The study also concludes that communication plays a vital role in the transfer of learning. That student-to-lecturer communication was the main issue around which both negative and positive perceptions towards ICTs were centered reveals this position. Accordingly, remote T&L's effectiveness is conceivably dependent on the ICTs communicative capabilities to facilitate lecturer-to-student engagement as well as student-to- student collaboration during the learning process. Taken together, the above demonstrates that indeed T&L during Covid-19 was a communication issue. Communication processes between lecturers and students as well as among students took place within a challenging environment influenced by different ICTs deployed for learning. For effective T&L (communication) to occur, the noises surrounding the whole process of communication needed to be moderated. This is because good content (message) alone may not be enough to achieve effective learning.
MA (Communication), North-West University, Mahikeng Campus
Keywords: Covid-19; Emergency remote learning; Students’ perceptions; Higher education; Information Communication Technologies (ICTs); NWU Mafikeng Campus; Teaching and Learning (T&L) as communication.